ON THE FORM OF KNOWLEDGE IN EDUCATION: REIFICATION AND SYMBOLIC VIOLENCE - D. KLUS-STANSKA (Высшее образование в России)
This article deals with the problem of educational changes. Education invariance is related to inertia of its forms and self-reproduction of vested teaching practices, but first of all – to the current epistemological regime in education. Orientation of educational system at scientific samples of knowledge dehumanizes pedagogical relations, mariginalizes students’ creative activity, and blocks the latter’s innovative-pedagogical processes. As a result, education becomes a hurdle on the way to cultural and social development. The author suggests a solution of the problem in the objectivization of the situation, as well as in the analysis and change of implicit functioning education forms.